Semantic use of the word came(ataa)and rooted in the Koran - سليم علي القريشي عزيز (Journal of College of Education, 2019)
This research examines an important aspect which semantic weighting on the contexts and changing the meaning my research was limited to studying the word came and showing its meaning depending on the pastries of the language and what found in the holy Quran and Arab heritage